Efficacy of oral methotrexate in paediatric Crohn's disease: a multicentre propensity score study. Issue 12 (21st November 2014) - Turner, Dan; Doveh, Etti; Cohen, Ayala; Wilson, Michelle L; Grossman, Andrew B; Rosh, Joel R; Lu, Ying; Bousvaros, Athos; Deslandres, Colette; Noble, Angela; Baldassano, Robert N; Levine, Arie; et al.
Abstract : Background: Oral methotrexate (MTX) administration avoids weekly injections, reduces costs and may improve quality of life of patients with Crohn's disease (CD), especially children. Routes of administration have never been systematically compared in CD. We aimed to compare effectiveness and safety of orally (PO) versus subcutaneously (SC) administered MTX in paediatric CD. Methods: 226 children with CD treated with oral or subcutaneous MTX were included in a multicentre, retrospective 1-year cohort study (62% boys, mean age 13.8±2.8 years, 88% previous thiopurines). 38 (17%) were initially commenced on oral, 98 (43%) started subcutaneous and switched to oral and 90 (40%) were treated with subcutaneous only. Matching and 'doubly robust' weighted regression models were based on the propensity score method, controlling for confounding-by-indication bias. 11/23 pretreatment variables were different between the groups, but the propensity score modelling successfully balanced the treatment groups. Results: 76 children (34%) had sustained steroid-free remission with a difference that did not reach significance between the PO and the SC groups (weighted OR=1.72 (95% CI 0.5 to 5.9); p=0.52). There were no differences in need for treatment escalation (p=0.24), elevated liver enzymes (p=0.59) or nausea (p=0.85). Height velocity was lower in the PO group (p=0.006) and time to remission was delayed in the PO group (p=0.036; Fleming (0, 1) test). Conclusions: In this largest paediatric CD cohort to date, SC administered MTX was superior to PO, but only in some of the outcomes and with a modest effect size. Therefore, it may be reasonable to consider switching children in complete remission treated with subcutaneous MTX to the oral route with close monitoring of inflammatory markers and growth.